136k views
0 votes
Use the table below to answer this question:

x y
-1 -3
0 -1
2 3

Find the average rate of change for the given function from x = −1 to x = 2.

A.) −2

B.)−1

C.)1

D.) 2

User Anil Shah
by
5.9k points

1 Answer

6 votes

Given:

The table of values.

To find:

The average rate of change for the given function from x = −1 to x = 2.

Solution:

From the given table it is clear that y=-3 at x=-1 and y=3 at x=2.

Formula for average rate of change is


m=(y_2-y_1)/(x_2-x_1)

Using the above formula, the average rate of change for the given function from x = −1 to x = 2 is


m=(3-(-3))/(2-(-1))


m=(3+3)/(2+1)


m=(6)/(3)


m=2

Therefore, the correct option is D.

User Visnu
by
5.5k points